2018
DOI: 10.1787/d7605f72-en
|View full text |Cite
|
Sign up to set email alerts
|

Financing innovative business investment in Poland

Abstract: JT03434116 This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. ECO/WKP(2018)28 Unclassified English-Or. English ECO/WKP(2018)28 2 OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author. Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…It is empirically confirmed that innovation activity of SMEs is limited by the accessibility of sufficient funds (Goujard and Guérin 2018;Hall 2010). In this respect, this study contributes to the ongoing debate on SMEs financing decisions and the existence of financing (capital) gap (Angilella and Mazzù 2015;De Moor et al 2016;Hottenrott and Peters 2012).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is empirically confirmed that innovation activity of SMEs is limited by the accessibility of sufficient funds (Goujard and Guérin 2018;Hall 2010). In this respect, this study contributes to the ongoing debate on SMEs financing decisions and the existence of financing (capital) gap (Angilella and Mazzù 2015;De Moor et al 2016;Hottenrott and Peters 2012).…”
Section: Introductionsupporting
confidence: 61%
“…Moreover, it seems that the system interventions mechanisms should not pursue a defined financing mix for the implementation of a given type of innovation. The core element of these mechanisms should be based on the alternative market-based financing instruments, which are crucial for access to the long-term sources of funds, as noted by Goujard and Guérin (2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the public and private capital stock is weak, and investment remains focused on the adoption of existing technologies, which weighs on future productivity gains and innovation. Many microenterprises have low productivity, and structural bottlenecks reduce start-ups' growth and their chances of survival [2].…”
Section: Resultsmentioning
confidence: 99%